COMPARATIVE ANALYSIS OF PHONETIC TESTS USED FOR ASSESSING THE SMILE DISPLAY - Cristina Teodora Preoteasa; Anca Axante; Ana Maria Hagiu; Anca Diana Cristea; Elena Preoteasa (Romanian Society of Oral Rehabilitation, 2016)
Aim. To comparatively analyze different phonetic tests used for assessing smile display, i.e. pronunciation of -ee‖ phoneme, -chee‖, -cheese‖, -Chester eats cheesecake by the Chesapeake‖. Methods. Registrations were made using videography. Subjects were placed sited, instructed to hold their head in a natural position, and asked to repeat five consecutive times each of the four phonetic tests, whose order was randomized. For horizontal display maximal intercommissural width was evaluated, and for vertical display the distance between stomion superius and the maximal incisal edge was analyzed. Results. Nineteen participants were included, 8 males and 11 females, aged 24 to 29 years old (mean 25 years). During speech, maximal horizontal display was observed while pronouncing -ee‖ phoneme, and maximal vertical display while saying -chee‖. While smiling, maximal horizontal and vertical display were rather similar for all four previously used phonetic tests. Paired t-test revealed that for all four named phonetic tests, during speech compared to a posed smile, the horizontal display was statistically significant reduced (the difference ranged from .65 to 1.56 of the width of the right central maxillary incisor) and maximal vertical display was rather similar. Conclusions. The mentioned phonetic tests seem more appropriate for the analysis of vertical smile display than for the horizontal smile display, for the latter a correction coefficient being most probably necessary. The use of a phonetic test followed by a posed social smile may positively contribute, through this -functional exercise‖, to obtaining a more natural outcome by decreasing the variability of the social smile acknowledged when using static methods.